2011
DOI: 10.1007/s10286-010-0098-y
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency power of heart rate variability reflects baroreflex function, not cardiac sympathetic innervation

Abstract: Objective Power spectral analysis of heart rate variability is used clinically to assess cardiac autonomic function. High frequency power is related to respiratory sinus arrhythmia and therefore to parasympathetic cardiovagal tone. The relationship of low frequency (LF) power to cardiac sympathetic tone is less clear. We reported previously that LF power may reflect baroreflex function; however, in the previous study LF power was not adjusted for possible influences of respiration. In this study we assessed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
4
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(209 citation statements)
references
References 26 publications
10
189
4
6
Order By: Relevance
“…Further, the LF/HF ratio has been suggested to offer a measure of sympathovagal balance (Malliani et al 1994), but this theory has conflicting arguments (Berntson et al 1997;Eckberg, 1997). A recent study of Rahman et al (2011) concluded, and replicated previous findings (Moak et al 2007), that LFP power does not reflect cardiac sympathetic tone but may reflect the ability of baroreflexes to modulate cardiac autonomic outflows. In addition, in the recent study of Ng et al (2009), -adrenergic blockade did not affect LFP during immediate recovery after exercise.…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…Further, the LF/HF ratio has been suggested to offer a measure of sympathovagal balance (Malliani et al 1994), but this theory has conflicting arguments (Berntson et al 1997;Eckberg, 1997). A recent study of Rahman et al (2011) concluded, and replicated previous findings (Moak et al 2007), that LFP power does not reflect cardiac sympathetic tone but may reflect the ability of baroreflexes to modulate cardiac autonomic outflows. In addition, in the recent study of Ng et al (2009), -adrenergic blockade did not affect LFP during immediate recovery after exercise.…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…The finding of decreased heart rate in group C also supports this interpretation of vagal regulation of blood pressure. A decrease in the percentage of the LF component was also found in group C, and this change reflects baroreflex modulation 17) . Hedman et al found that HF reflects the parasympathetic regulation of the heart, i.e.…”
Section: Discussionmentioning
confidence: 66%
“…In this context, the LF index of HRV is also considered an indicator of baroreflex function [12,20]. It was previously observed that during hemodialysis hypotensive events were associated with significant increases in LF and HF frequency domain indices and also in baroreflex function [11].…”
Section: Discussionmentioning
confidence: 99%